2019
DOI: 10.1021/acsanm.9b00977
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Magnetic Supraparticles with a Magnetic Particle Spectroscopy Fingerprint as Indicators for Cold-Chain Breach

Abstract: Magnetic particle spectroscopy (MPS) is used in this work to obtain a magnetic fingerprint signal from anisotropic supraparticles, i.e., microrods assembled from superparamagnetic iron oxide nanoparticles. Exceeding its intended purpose of nanoparticle characterization for biomedical magnetic particle imaging, it is shown that MPS is capable of resolving structural differences between the anisotropic alignment of individual nanoparticles and its isotropic counterpart. Additionally, orientation-dependent MPS si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
(34 reference statements)
1
28
0
Order By: Relevance
“…In our previous published studies, we reported that the Di/Tri sample showed the best heating efficiency due to the linear magnetic dipolar coupling in the system that affects the overall magnetic property of the nanocube assembly [ 24 ]. These finding for the Di/Tri sample is also in good agreement with the recent MPI relaxometry study of Müssig et al on anisotropic rod-like microscale assemblies of MNPs [ 32 ]. The authors reported, the preparation under a permanent magnet (0.12 T) of meso/microscale rod-like assemblies of multiple superparamagnetic nanoparticles of an average size of 10 nm coated by a silica shell, which exhibited a 14-fold improvement in MPI signal, in comparison to isotropic aggregates (150 nm to 8 µm assemblies produced in the absence of a magnetic field gradient) and individual particles.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In our previous published studies, we reported that the Di/Tri sample showed the best heating efficiency due to the linear magnetic dipolar coupling in the system that affects the overall magnetic property of the nanocube assembly [ 24 ]. These finding for the Di/Tri sample is also in good agreement with the recent MPI relaxometry study of Müssig et al on anisotropic rod-like microscale assemblies of MNPs [ 32 ]. The authors reported, the preparation under a permanent magnet (0.12 T) of meso/microscale rod-like assemblies of multiple superparamagnetic nanoparticles of an average size of 10 nm coated by a silica shell, which exhibited a 14-fold improvement in MPI signal, in comparison to isotropic aggregates (150 nm to 8 µm assemblies produced in the absence of a magnetic field gradient) and individual particles.…”
Section: Resultssupporting
confidence: 91%
“…The authors reported, the preparation under a permanent magnet (0.12 T) of meso/microscale rod-like assemblies of multiple superparamagnetic nanoparticles of an average size of 10 nm coated by a silica shell, which exhibited a 14-fold improvement in MPI signal, in comparison to isotropic aggregates (150 nm to 8 µm assemblies produced in the absence of a magnetic field gradient) and individual particles. This unique enhancement was claimed to depend on the chain-like anisotropic assembling of the MNPs rather than the intrinsic property of individual nanoparticles used as building blocks [ 32 ]. Moreover, the reduced MPI signal of the 3D-Clusters we observed, is likely attributed to the random magnetic dipole interactions in the centrosymmetric cluster system [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is, as upon agglomeration of magnetic nanoparticles, their close proximity strongly alters their magnetic properties in the utilized setup. [37][38][39] Thus, the hierarchical approach prevents strong coupling of individual nanoparticles [40] and is key to distinguish different compositions by MPS. The different supraparticles can still be easily distinguished after several weeks of storage in ambient conditions, which is essential for a functional marker (see Figure S10, Supporting Information).…”
Section: Adapting the Principle Of A Musical Ensemble To Create An Advanced Magnetic Marker Supraparticlementioning
confidence: 99%
“…Cold chain breach indicating magnetic supraparticulate microrods have been described by Müssig et al. [ 208 ] Besides other mechanical stress indicator SPs, [ 209 ] a shear indicator based on hierarchically structured luminescent dye‐doped silica NPs and iron oxide NPs assembled via spray‐drying has been established. [ 207 ] It reports damages, e.g., by an increase in fluorescence signal (Figure 11c).…”
Section: Supraparticles For Sustainabilitymentioning
confidence: 99%